Processes of Political Violence and the Dynamics of Situational Interaction - Malthaner, Stefan (International Journal of Conflict and Violence (IJCV), 2017)
This paper explores how processual approaches to political violence, which largely focus on patterns of strategic interaction at the meso-level of analysis, can be enhanced by paying closer attention to conditions, patterns, and the micro-dynamics of violence in face-to-face encounters. Discussing characteristic elements of processual and situational approaches, and drawing on brief vignettes of episodes of violence in political conflicts in Peru, Egypt, and Germany, it argues that the theoretical value of this perspective is twofold. Firstly, it allows us to capture unintended outcomes of situational interactions, which can account for the sudden emergence or escalation of violence. Secondly, it argues that situational interaction approaches can refine our understanding of meso-level violent processes because they allow us to examine how these processes shape and “produce” situational conditions and constraints that facilitate and induce violent escalation and thus offer ways to capture and conceptualize complex patterns of enchainment.